Quality of life among geriatric population residing in Bhavnagar city, Gujarat, Western India - Bansi Trivedi (Journal of Family Medicine and Primary Care, 2023)
Background: All of the health status, lifestyle, satisfaction, mental state, or well-being, all facets of health status together reflect the multidimensional nature of quality of life (QOL) in an individual. Our objective is to assess quality of life and factors affecting quality of life. Methods: We conducted a community-based cross-sectional study among 260 subjects (aged ≥ 60 years) residing in 13 wards of Bhavnagar city during September 2019–2020 after taking permission from ethics committee (no. 892) using the World Health Organization Quality of Life BREF-25 (WHO QOL BREF-25) scale. We assessed psychiatric morbidity using General Health Questionnaire-12 scale. Independent t-test was performed to find out factors associated with quality of life. Result: Among 260 subjects, 36% were males. Study found highest score in psychological domain and lowest score in physical domain of WHO QOL BREF-25 scale. Physical health was better among Muslims, geriatrics <75 year of age, not addicted abusive substance and no co-morbid condition, whereas geriatrics belonged to upper socio-economic status and normal as per General Health Questionnaire-12 scale had better social relationship. Environmental domain score was significantly better among males and geriatric without co-morbidity. Conclusion: These findings highlight the importance of active ageing interventions in order to improve the quality of life.